Management of the Indonesian Basketball Association (PERBASI) Banyumas Regency in 2020 (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The purpose of this study is to analyze the planning system in PERBASI Banyumas Regency, to analyze the organizing system in PERBASI Banyumas Regency, analyze the implementation system in PERBASI Banyumas Regency, and to analyze controling system in PERBASI Banyumas Regency. The research methods is descriptive qualitative. The data information was collect from the Chief Executive of PERBASI Banyumas Regency, the General Secretary of PERBASI Banyumas Regency, the Head Coach of PERBASI Banyumas Regency, the Referee of PERBASI Banyumas Regency and the General Secretary of KONI Banyumas Regency. Data collection techniques in this study using observation, interviews, and documentation. The result showed that the Planning system is already exist, but not been implemented properly. The organizing system is well structured, the composition of the management is stated in a decree from the Regional Management of PERBASI, Central Java Province. The process of implementing work programs or activities has not been implemented due the corona virus. The evaluation has been going well. The conclusion is the planning system in PERBASI Banyumas Regency management in very good category because in planning system meets all the planning criteria of sport organizations. Organizing system in PERBASI Banyumas Regency management included in category good and the implementation system in PERBASI Banyumas Regency management include in good category because it has not meets the criteria of sports organizations. And the controlling system in PERBASI Banyumas Regency management is included in the sufficient category.